Osteocalcin and Metabolic Syndrome - Consolim-Colombo, Fernanda M; Ferreira Lopes, Heno (Scripta Medica, 2025)
This mini-review examines the multifaceted roles of osteocalcin, a bone-derived protein that functions as a critical mediator between skeletal biology and systemic metabolism. We explore osteocalcin's dual functions: its canonical role in bone mineralisation and structural integrity and its emerging significance as an endocrine regulator of energy homeostasis. The review synthesises current evidence regarding the distinct biological activities of carboxylated and undercarboxylated osteocalcin forms, their relationship with metabolic syndrome parameters and interactions with the autonomic nervous system. Additionally, we evaluate therapeutic interventions that modulate osteocalcin levels, potentially offering novel approaches for addressing metabolic disorders. By integrating findings from molecular, animal and clinical studies, this review aims to provide a comprehensive understanding of osteocalcin's physiological significance and its potential applications in metabolic health management, highlighting the bone-energy metabolism axis as an important frontier in endocrine research.